2010
DOI: 10.13073/0015-7473-60.6.508
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Performance of Engineered Wood Flooring with Oriented Strand Board Substrate

Abstract: Plywood is widely used as a substrate in engineered wood flooring (EWF) construction. While the Canadian EWF industry largely relies on Baltic birch plywood (BBP), the development of an alternative substrate is clearly desirable. The objective of this study was to evaluate the long-term performance of EWF made with an oriented strand board (OSB) substrate designed to deliver a higher than normal internal bond. Three-layer OSB panels were made from a mixture of 90 percent aspen (Populus tremuloides) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The equivalence of accelerated and outdoor weathering Outdoor weathering was designed in this study with the purpose of study the lifespan of BPP as well as establish comparison to laboratory aging. Previous research [7][8] showed both reversible and irreversible dimension changes were known to occur as a result of water absorption and desorption, stress take place due to unbalanced dimension variation, stress transfer and build-up in fibers and bond interface and controlled by the interfacial strength and integrity of the panels. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The equivalence of accelerated and outdoor weathering Outdoor weathering was designed in this study with the purpose of study the lifespan of BPP as well as establish comparison to laboratory aging. Previous research [7][8] showed both reversible and irreversible dimension changes were known to occur as a result of water absorption and desorption, stress take place due to unbalanced dimension variation, stress transfer and build-up in fibers and bond interface and controlled by the interfacial strength and integrity of the panels. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the prolonged durability of engineered wood flooring is crucial, especially considering the influence of heat and moisture fluctuations. Blanchet (2008) revealed that most adhesive, except for epoxy adhesive, demonstrated comparable performance. The utilization of epoxy adhesive resulted in notable inconsistencies and delamination in the structures.…”
Section: Adhesive Sticking Propertiesmentioning
confidence: 95%
“…All of the samples were provided by Dare (Jiangsu) Parquet of Jiangsu, China. According to the different properties of the substrate layers (9 mm thick poplar or 2 mm thick poplar/seven layer plywood), the floorings samples for the 9 mm thick poplar panels had two types of surface layers tested (structures A and B), whereas the 2 mm thick poplar/seven layer plywood panels were labeled structure C (Blanchet et al 2008;Barbuta et al 2010). The two types of surface layers used for the 9 mm thick poplar panels were: structure A, which contained a 4 mm thick decorative veneer surface layer and a 2 mm thick poplar veneer as backing layer (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that substrates and surface components will impact long-term performance properties, such as aging resistance. Of the adhesives tested, epoxy exhibited poor gluing and delamination, whereas EPl adhesives exhibited the best performance in terms of aging (Blanchet 2008). Other research (Fang et al 2012a,b) has explored the use of oil-heat treatment applied to densified wood to reduce the hygroscopicity and improve mechanical properties of wood veneers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation